Nidā’ Al-Qur’an: A Study of the Manuscript of Tafsīr Yā Ayyuha Al-Lażīna Āmanū by Shaykh Abdul Latief Syakur 20th Century - Wahidi, Ridhoul (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
The study of the Qur’anic nidā' is important to understand and master and distinguish the khitab to whom the call is addressed and what the meaning or essence of the call is conveyed. The purpose of this study is to explore and find the context of the call (nidā'), khitāb and mukhātab addressed in Tafsīr Yā Ayyuha Al-Lażīna Āmanū. This article theoretically and methodologically has an important role in the study of al-Qur'anic sciences and tafsir. This research is a library research with philological method with philosophical historical approach and analyzed with descriptive analysis model. The findings in this study indicate that there are three contexts addressed in the existence of nidā' verses. First, nidā' verses whose mukhātab clearly refer to individuals. Second, nidā' verses refer to a particular community either in general or in particular. Thirdly, nidā' verses whose mukhātab refers to a particular community either generally or specifically. Of all the nidā' in this tafsir, the khitab nidā' are categorized into five: nidā' related to the relationship between man and God; nidā' related to the relationship between the believing servant and the Prophet Muhammad; nidā' related to the relationship between people and their families; and nidā' related to the relationship between believers and disbelievers and disobedient people. Kajian nidā’ al-Qur’an penting dilakukan guna memahami dan menguasai serta membedakan khitab kepada siapa seruan itu ditujukan dan apa makna atau esensi seruan tersebut disampaikan. Adapun tujuan penelitian ini untuk menggali dan menemukan konteks seruan (nidā’), khitāb dan mukhātab yang dituju dalam Tafsīr Yā Ayyuha Al-Lażīna Āmanū. Artikel ini secara teoritis dan metodologis memiliki peran penting dalam studi ilmu-ilmu al-Qur’an dan tafsir. Penelitian ini adalah penelitian kepustakaan (Library Reseach) dengan motode filologi dengan pendekatan historis filosofis dan dianalisa dengan model deskriptif-analisis (descriptive analysis). Temuan dalam penelitian ini menunjukkan bahwa ada tiga konteks yang dituju pada eksistensi ayat-ayat nidā’. Pertama, ayat-ayat nidā’ yang mukhātabnya jelas merujuk kepada individu. Kedua, ayat-ayat nidā’ mengacu pada komunitas tertentu baik secara umum atau khusus. Ketiga, ayat-ayat nidā' yang tujuan mukhātabnya masih menimbulkan penafsiran tentang siapa sebenarnya yang dimaksud. Dari keseluruhan nidā' dalam tafsir ini, khitab nidā’nya dikelompokkan menjadi lima, yakni nidā’ yang terkait hubungan antara manusia dan Tuhan; nidā’ yang terkait antara hamba yang beriman dengan Nabi Muhammad; nidā’ yang terkait dengan antara orang dengan keluarga mereka; dan nidā’ yang terkait antara orang beriman dengan orang kafir dan durhaka.